Neglected and underutilized crop species in Kabare and Walungu territories, Eastern D.R. Congo: Identification, uses and socio-economic importance - Jean M. Mondo (Elsevier, 2021)
Neglected and underutilized crop species (NUCS) are valuable sources of food and income for several rural households in the eastern Democratic Republic of Congo (DRC). A thorough understanding of their diversity, uses, socio-economic roles, and factors for their neglect would be necessary for guiding promotion efforts. This study was conducted in two steps: (1) interviews with rural households involved in NUCS production and trade, and (2) greenhouse characterization of the two most popular NUCS′ morphotypes, African nightshade and amaranth, from Walungu and Kabare territories, eastern DRC. About 19% of farmers of the entire study area were involved in NUCS production. We identified 22 and 23 NUCS used in Kabare and Walungu territories, respectively. These species belonged to 19 botanical families, among which Solanaceae (∼24% in Walungu and ∼11 in Kabare) and Fabaceae (8% in Walungu and 11% in Kabare) were the most dominant families. They were of different ranges: grasses and herbs (62%), shrubs (20%), thorns (2%), and trees (16%). These species were used whether for nutritional (60%), medicinal (7%), or both nutritional and medicinal values (33%). NUCS' market value was low, and thus, discouraged further investment in their farming. The seed delivery system was informal, dominated by farmer-saved seed, seed from local markets, and farmer seed exchange. Characterization experiment for the most popular leafy NUCS showed differences among collected morphotypes for most traits, with some local genotypes outperforming exogenous commercial varieties. Supply of quality seed, training of farmers on the most appropriate cropping system, processing technologies, increased consumer awareness, linking research to policy, and increasing market opportunities for smallholder farmers are strategies for promoting wide use of these crops in eastern DRC.